Towards an inclusive and developmental housing regime in Chinese megacities? Evidence from the implementation of the Affordable Rental Housing Programme in Shanghai - Zhou, Lin; Chen, Chen (AESOP, 2024)
Affordable Rental Housing (ARH) is the latest social rental housing programme proposed by the Chinese government, which forms part of the social housing system and is primarily designed to alleviate the housing difficulties of the inflowing new citizens and young people in megacities, thus moving towards a developmental housing regime. Focusing on the implementing process of the ARH program in Shanghai, this study observed the location of ARH in the housing system, the project types, provision mode, spatial distribution, and affordability of ARH, then explored the tensions between the government and stakeholders through the conceptual lens of governance structure. This study enriches the conceptual and empirical understanding of ARH in China and enriches the understanding of housing regime transformation in China. Keywords: housing regime, rental housing system, affordable rental housing (ARH), public rental housing (PRH), Shanghai
Game changer? Planning for just and sustainable urban regions, Paris, 8-12th July 2024